Suspension flow with deposition in lung airway bifurcations in different breathing conditions - Miguel, A. F. (2012)
Flow of suspension of aerosols in airway bifurcations during breathing is important in the field of industrial hygiene, in the administration of therapeutic drugs by inhalation, and in the diagnosis of pulmonary diseases. This chapter reports the development of a combined analytical and experimental technique for assessing the behavior of aerosol deposition in bifurcation airways. The aerosol deposition efficiency in terms of the tidal volume, breathing frequency, geometrical characteristics of airways and aerosol particles was derived analytically. Besides, an experimental study is reported in triple bifurcation models with geometries similar to bronchi airways (i.e., generations 1 to 3 of the respiratory system), under healthy and asthma constricted conditions. Breathing patterns consistent with sedentary and light activity were employed. Experiments were performed near the air saturation (relative humidity 95+-4%) with aerosol particles ranging from 0.6 to 31 micron in diameter. These conditions correspond to Stokes numbers ranging from 0.014 to 0.26. The results showed that aerosol deposition decreased in the successive bifurcations and increased with the airway constriction. Moreover, the aerosol particle size and breathing characteristics were found to influence significantly the degree of aerosol deposition. In addition, there is a satisfactory agreement between the model predictions and the experimental data.